The development and reliability of a repeated anaerobic cycling test in female ice hockey players - Wilson, K.; Snydmiller, G.; Game, A.; Quinney, A.; Bell, G. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to develop and assess the reliability of a repeated anaerobic power cycling test designed to mimic the repeated sprinting nature of the sport of ice hockey. Nineteen female varsity ice hockey players (x¯ ± SD age, height and body mass = 21 ± 2 yr, 166.6 ± 6.3 cm and 62.3 ± 7.3) completed 3 trials of a repeated anaerobic power test on a Monark cycle ergometer on different days. The test consisted of "all-out" cycling for 5 seconds separated by 10 seconds of low-intensity cycling, repeated 4 times. The relative load factor used for the resistance setting was equal to 0.095 kg per kilogram body mass. There was no significant difference between the peak 5-second power output (PO), mean PO, or the fatigue index (%) among the 3 different trials. The peak 5-second PO was 702.6 ± 114.8 w and 11.3 ± 1.1 w/kg, whereas the mean PO across the 4 repeats was 647.1 ± 96.3 w and 10.4 ± 1.0 w/kg averaged for the 3 different tests. The fatigue index averaged 17.8± 6.5%. The intraclass correlation coefficient for peak 5-second, mean PO, and fatigue index was 0.82, 0.86, and 0.82, respectively. This study reports the methodology of a repeated anaerobic power cycling test that was reliable for the measurement of PO and calculated fatigue index in varsity women ice hockey players and can be used as a laboratory-based assessment of repeated anaerobic fitness.